ILT4 drives B7‐H3 expression via PI3K/AKT/mTOR signalling and ILT4/B7‐H3 co‐expression correlates with poor prognosis in non‐small cell lung cancer. Issue 17 (3rd July 2015) - Zhang, Pei; Yu, Shuwen; Li, Hongyu; Liu, Chuanyong; Li, Juan; Lin, Wenli; Gao, Aiqin; Wang, Linlin; Gao, Wei; Sun, Yuping
Abstract : Immunoglobulin‐like transcript (ILT) 4 is critical for the inhibitory function of certain immune cells. We previously demonstrated that ILT4 is over‐expressed in human non‐small cell lung cancer (NSCLC) cells and is involved in tumour evasion via an unknown mechanism. In this report, we demonstrate that ILT4 increases the expression of the co‐inhibitory molecule B7‐H3 through PI3K/AKT/mTOR signalling. In primary human NSCLC tissues, a significant positive relationship is observed between ILT4 and B7‐H3 expression. ILT4/B7‐H3 co‐expression is significantly associated with a reduction in T infiltrating lymphoid cells and lower overall survival. In summary, ILT4 increases B7‐H3 expression and ILT4/B7‐H3 co‐expression may be involved in NSCLC progression. Abstract : ILT4 drives typical co‐inhibitory molecule B7‐H3 expression in NSCLC cells. ILT4 activated PI3K/AKT/mTOR signalling in NSCLC cells. ILT4 drives B7‐H3 expression via PI3K/AKT/mTOR signalling in NSCLC cells. ILT4 and B7‐H3 are co‐expressed in NSCLC cell lines and tissues. ILT4 and B7‐H3 co‐expression is correlated with fewer T infiltrating lymphoid cells and worse survival.